Kritik Sosial dalam Lirik Lagu Album Akibat Pergaulan Blues Karya Musisi Jason Ranti - Faisal, Abiyyu Farras; Hasanuddin WS (Universitas Negeri Padang, 2024)
Jason Ranti, in the lyrics of his album entitled The Effects of Blues Association, conveys a lot of criticism and satire on social problems which are considered problems by society depending on the social value system of that society, however there are the same problems faced by society in general, for example the problem of poverty and crime. , family disorganization, the younger generation in modern society, war, violations of societal norms, population, the environment, and bureaucracy. This type of research is qualitative. According to Semi (1993:23), qualitative research is carried out without prioritizing numbers, but prioritizing the depth of appreciation of the interactions between concepts that are being studied empirically. This research using qualitative methods cannot be measured, because its nature emphasizes socially constructed reality. Data from the results of this research found social criticism in the song lyrics in Jason Ranti's album Akun Pergaulan Blues as many as 24 data in the form of several fragments of song lyrics which include 3 types of social criticism, namely (1) social criticism about violations of societal norms (2) social criticism about religious behavior and beliefs (3) social criticism about politics and bureaucracy. It can be concluded that the social criticism contained in the lyrics of the song Album